Discovery of substantial Oxalis (Oxalidaceae) diversity and endemism in an arid biodiversity hotspot - Oberlander, Kenneth Carl; Roets, Francois; Dreyer, Leanne Laurette (Phytotaxa, 2014)
Despite globally acknowledged diversity levels, the flora of the arid Richtersveld of South Africa remains poorly known for certain plant lineages, including the eudicot genus Oxalis. Cryptic habit, inaccessible and harsh terrain and the lack of focussed systematic attention has led to the assumption that the region is depauperate in this genus. However, recent exploration proved quite the opposite and revealed a wealth of Oxalis species, including at least ten undescribed species and many significant range extensions of known taxa. We are in the process of describing these new species, but an overarching work, placing the abundant new knowledge in the context of southern African Oxalis, is necessary. In this study we revise the state of knowledge regarding Richtersveld Oxalis and provide brief descriptions, diagnostic characters and a morphological identification key for the 20 species confirmed to occur in the region. Nine of the ten new species are currently only known from the Richtersveld, with seven having extremely limited known distributions. Surprisingly, levels of endemism in the Richtersveld are higher than the relatively well-explored central Namaqualand Oxalis flora, and suggest that, far from being depauperate in Oxalis, the Richtersveld region should be considered a centre of endemism for the genus in southern Africa.